Updating civil legislation in accordance with European quality standards: the example of Ukraine - Shyshka, R. B.; Шишка, Р. Б.; Shyshka, O. R.; Шишка, О. Р.; Shishka, N. V.; Шишка, Н. В.; Slipchenko, A. S.; Сліпченко, А. С.; Tkalych, M. O.; Ткалич, М. О. (DIXI. – 2022. – Vol. 24, № 1 (enero-junio). – P. 1-27, 2022)
Стаття присвячена дослідженню європейських стандартів якості права для сприяння ефективності розпочатої в Україні роботи з оновлення цивільного законодавства. Можливість досягнення цієї мети залежить від якості процесу. Такий процес насамперед сприяє утвердженню абсолютної цінності людської особистості, свободи, демократії, рівності, пріоритету людини над державою; удосконалення механізмів захисту та належного захисту прав і свобод людини, її рівності перед законом і справедливістю.

The article is devoted to the study of European quality standards of the law to promote the effectiveness of the work begun in Ukraine on updating the civil legislation. The ability to achieve this goal depends on the quality of the process. Such a process primarily contributes to the assertion of the absolute value of the human person, freedom, democracy, equality, and the priority of man over the state; improving the mechanisms of protection and proper protection of human rights and freedoms, their equality before the law and justice. The latter especially in the context of counteracting the spread of the covid-19 pandemic, which has led the state of Ukraine (as well as other states) to take steps to limit or reduce human rights and, accordingly, is not always compatible with the rule of law. General and special methods of scientific knowledge were used in this study, namely methods: Analysis and synthesis, systems analysis, formal-logical and structural-functional, along with some empirical methods. The practical significance of the study is that the materials summarized in the research and the conclusions reached by the authors are relevant for foreign legislators, regarding bringing national legislation to global trends in private law and its compliance with the rule of law, including the principle of legal certainty and legitimate expectations. Based on the analysis of the European Court of Human Rights (echr) practice and other European Union requirements for the quality of law in Europe, the authors made several conclusions and recommendations on the process of updating the civil legislation of Ukraine. At the same time, the update in its systemic manifestation should concern not only the quality of norms governing certain civil (private) relations, but also the quality of norms regarding acts of the causal interpretation of legal norms, based on the case-law of the echr for national legislation and special requirements.

Статья посвящена изучению европейских стандартов качества права для повышения эффективности начатой в Украине работы по обновлению гражданского законодательства. Возможность достижения этой цели зависит от качества процесса. Такой процесс прежде всего способствует утверждению абсолютной ценности человеческой личности, свободы, демократии, равенства, приоритета человека над государством; совершенствование механизмов защиты и надлежащей защиты прав и свобод человека, их равенство перед законом и правосудием.

El artículo está dedicado al estudio de las normas europeas de calidad de la ley para promover la eficacia del trabajo iniciado en Ucrania sobre la actualización de la legislación civil. La capacidad de alcanzar este objetivo depende de la calidad del proceso. Dicho proceso contribuye principalmente a la afirmación del valor absoluto de la persona humana, de la libertad, de la democracia, de la igualdad y de la prioridad del hombre sobre el Estado; a la mejora de los mecanismos de protección y de la correcta defensa de los derechos y libertades humanas, de su igualdad ante la ley y de la justicia. Esto último, especialmente en el contexto de la lucha contra la propagación de la pandemia de la covid-19, que ha llevado al Estado de Ucrania (así como a otros Estados) a tomar medidas para limitar o reducir los derechos humanos, y en consecuencia, no siempre es compatible con el Estado de Derecho. En este estudio, se utilizaron métodos generales y especiales del conocimiento científico, a saber: métodos de análisis y síntesis, análisis de sistemas, formal-lógico y estructural-funcional, junto con algunos métodos empíricos. La importancia práctica del estudio radica en que los materiales resumidos en la investigación y las conclusiones a las que han llegado los autores son relevantes para los legisladores extranjeros, en lo que respecta a la adaptación de la legislación nacional a las tendencias mundiales en materia de derecho privado y su conformidad con el Estado de Derecho, incluido el principio de seguridad jurídica y de confianza legítima. Basándose en el análisis de la práctica del Tribunal Europeo de Derechos Humanos (tedh) y otros requisitos de la Unión Europea para la calidad del derecho en Europa, los autores formularon varias conclusiones y recomendaciones sobre el proceso de actualización de la legislación civil de Ucrania. Al mismo tiempo, la actualización en su manifestación sistémica debe referirse no solo a la calidad de las normas que rigen determinadas relaciones civiles (privadas), sino también a la calidad de las normas relativas a los actos de la interpretación causal de las normas jurídicas, sobre la base de la jurisprudencia del tedh para la legislación nacional y requisitos especiales.
Actualización de la legislación civil de acuerdo con los estándares de calidad europeos: el ejemplo de Ucrania
Atualizar a legislação civil de acordo com os padrões de qualidade europeus: o exemplo da Ucrânia
Keywords: publikatsii u WoS; pandemic covid-19; principle of legal certainty; principle of rule of law; quality standards of law; re-codification; COVID-19; пандемія; принцип правової визначеності; принцип верховенства права; стандарти якості права; повторна кодифікація; принцип правовой определенности; принцип верховенства закона; стандарты качества права; рекодификация